Analysis of the Level of Public Knowledge about Self-Medicine, Gastritis, in Sharia Pharmacies - Noviani, Mila Audina; Rosmiati, Meiti (Journal of Scientific Insights, 2025)
Gastritis is a common gastrointestinal disorder that can lead to serious complications if not properly managed. Self-medication is a widely practiced method for relieving gastritis symptoms, but improper use of medications without adequate knowledge may result in adverse effects. This study aims to assess the public’s knowledge and behavior regarding self-medication for gastritis and examine its association with educational background, with a specific focus on the setting of a Sharia-based pharmacy. A descriptive cross-sectional design was used, involving 100 respondents selected through purposive sampling. Data was collected via online questionnaires and analyzed using chi-square tests. The findings show that the majority of respondents were aged 16–24 years and primarily obtained self-medication information from the internet (33%), followed by pharmacists (31%) and family or friends (26%). Despite the expectation that higher education correlates with better knowledge, the analysis showed no statistically significant relationship between education level and knowledge (p = 0.430), nor between education and self-medication behavior (p = 0.085). Furthermore, 94% of respondents reported never having practiced self-medication for gastritis. These results suggest a disconnect between access to information and actual health behavior. The study highlights the growing reliance on digital health sources and the persistent gap in health literacy, emphasizing the need for more structured and accessible health education to promote safe and responsible self-medication practices in the community, particularly among youth